LEGAL LIABILITY OF PERPETRATORS OF DOMESTIC VIOLENCE: AN INTEGRATED PERSPECTIVE OF CRIMINAL AND CIVIL LAW IN THE PROTECTION OF VICTIMS - Gunawan Widjaja (INJOSEDU: International Journal of Social and Education, 2026)
Domestic violence is a form of legal and human rights violation that causes physical, psychological, sexual and economic harm to victims within the household. Law No. 23 of 2004 emphasises that the elimination of domestic violence is aimed at preventing violence, prosecuting perpetrators and protecting victims; consequently, its handling cannot be limited solely to private family matters. This study aims to analyse the legal liability of perpetrators of domestic violence through an integrated perspective of criminal and civil law in the protection of victims. The method used is a literature review, examining legislation, legal literature, and relevant academic sources regarding domestic violence, victim protection, restitution, and the restoration of victims’ rights. The findings indicate that criminal legal liability serves to affirm prohibitions, establish the perpetrator’s guilt, and impose sanctions as a form of accountability for acts of domestic violence. However, a criminal approach alone is insufficient, as victims often suffer multiple layers of harm requiring concrete redress through civil mechanisms, including claims for damages and restitution. Perma No. 1 of 2022 strengthens victim recovery by stipulating that restitution may take the form of compensation for loss of wealth or income, material and immaterial losses, medical and psychological care costs, as well as other losses directly related to the criminal offence. Thus, the protection of victims of domestic violence demands an integrated approach between criminal and civil law so that justice does not merely end with the punishment of the perpetrator, but also provides effective redress, ongoing protection, and a guarantee of dignity for the victim.